PERSINGGUNGAN ISLAM DAN TRADISI MISTIK LOKAL: STUDI KASUS PANANYAAN DAN AHLI HIKMAH DI MASYARAKAT TASIKMALAYA - Asep Nahrul Musadad (Indonesian Journal of Islamic Literature and Muslim Society, 2016)
AbstrakOne of the determinant factors in the process of Islamization of the archipelago is the intersection between Islamic teachings and local wisdom. The encounter of the two has apparently brought an esoteric way. In this case, the Islamic esoteric teaching namely Sufism has become important. However, there was another esoteric element which also has a main role in the process, namely the mystical insight as to the result of the synthesis of the Islamic esoteric teaching and the indigenous mystical tradition. Using the ethnographic approach, this article aims to provide a preliminary remark on the intersection between Islam and local mystic tradition as represented by “pananyaan” and “ahli hikmah” in Sundanese people, especially in Tasikmalaya, as the reference. He is regarded as the “learned man” a place for someone to ask, especially related to the world of unseen.